Metagenomic signatures reveal the key role of phloretin in amelioration of gut dysbiosis attributed to metabolic dysfunction-associated fatty liver disease by time-dependent modulation of gut microbiome - Chhimwal, Jyoti; Anand, Prince; Mehta, Priyanka; Swarnkar, Mohit Kumar; Patial, Vikram; Pandey, Rajesh; Padwad, Yogendra (Frontiers in Microbiology, 2023)
The importance of gut-liver axis in the pathophysiology of metabolic dysfunction-associated fatty liver disease (MAFLD) is being investigated more closely in recent times. However, the inevitable changes in gut microbiota during progression of the disease merits closer look. The present work intends to assess the time-dependent gut dysbiosis in MAFLD, its implications in disease progression and role of plant-derived prebiotics in its attenuation. Male C57BL/6J mice were given western diet (WD) for up to 16 weeks and phloretin was administered orally. The fecal samples of mice were collected every fourth week for 16 weeks. The animals were sacrificed at the end of the study and biochemical and histological analyses were performed. Further, 16S rRNA amplicon sequencing analysis was performed to investigate longitudinal modification of gut microbiome at different time points. Findings of our study corroborate that phloretin alleviated the metabolic changes and mitigated circulating inflammatory cytokines levels. Phloretin treatment resists WD induced changes in microbial diversity of mice and decreased endotoxin content. Prolonged exposure of WD changed dynamics of gut microbiota abundance and distribution. Increased abundance of pathogenic taxa like Desulfovibrionaceae, Peptostreptococcus, Clostridium, and Terrisporobacter was noted. Phloretin treatment not only reversed this dysbiosis but also modulated taxonomic signatures of beneficial microbes like Ruminococcus, Lactobacillus, and Alloprevotella. Therefore, the potential of phloretin to restore gut eubiosis could be utilized as an intervention strategy for the prevention of MAFLD and related metabolic disorders.